Heritable Differences in Catecholamine Signaling Modulate Susceptibility to Trauma and Response to Methylphenidate Treatment: Relevance for PTSD - Deslauriers, Jessica; Toth, Mate; Zhou, Xianjin; Risbrough, Victoria B. (Frontiers in Behavioral Neuroscience, 2019)
Alterations in cortical catecholamine signaling pathways can modulate acute and enduring responses to trauma. Heritable variation in catecholamine signaling is produced by a common functional polymorphism in the catechol-O-methyltransferase (COMT), with Val carriers exhibiting greater degradation of catecholamines than Met carriers. Furthermore, it has recently been suggested that drugs enhancing cortical catecholamine signaling may be a new therapeutic approach for posttraumatic stress disorder (PTSD) patients. We hypothesized that heritable differences in catecholamine signaling regulate the behavioral response to trauma, and that methylphenidate, a drug that preferentially blocks catecholamine reuptake in the prefrontal cortex, exerts COMT-dependent effects on trauma-induced behaviors. We first examined the contribution of the functional mutation COMTval158met to modulate enduring behavioral response to predator stress in a unique “humanized” COMTval158met mouse line. Animals were exposed to a predator (cat) for 10 min and enduring avoidance behaviors were examined in the open field, light-dark box, and “trauma-reminder” tests 1-2 weeks later. Second, we examined the efficacy of chronic methylphenidate to reverse predator stress effects and if these effects were modulated by COMTval158met genotype. Mice were exposed to predator stress and began treatment with either saline or methylphenidate (3 mg/kg/day) 1 week after stress until the end of the testing (avoidance behaviors, working memory, and social preference). In males, predator stress and COMTval158met had an additive effect on enduring anxiety-like behavior, with Val stressed mice showing the strongest avoidance behavior after stress compared to Met carriers. No effect of COMT genotype was observed in females. Therefore methylphenidate effects were investigated only in males. Chronic methylphenidate treatment reversed the stress-induced avoidance behavior and increased social investigation independently of genotype. Methylphenidate effects on working memory however were genotype-dependent, decreasing working memory in non-stressed Met carriers, and improving stress-induced working memory deficit in Val carriers. These results suggest that heritable variance in catecholamine signaling modulates the avoidance response to an acute trauma. This work support recent human findings that methylphenidate might be a therapeutic alternative for PTSD patients and suggests that methylphenidate effects on anxiety (generalized avoidance, social withdrawal) vs. cognitive (working memory) symptoms may be modulated through COMT-independent and dependent mechanisms respectively.